2013
DOI: 10.1259/bjr.20130390
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance evaluation of spot scanning beam proton therapy with an anthropomorphic prostate phantom

Abstract: , and the results were compared between the treatment planning system (TPS) and RPC measurements.Results: RPC results show that the right/left, inferior/superior and posterior/anterior aspects of the coronal/sagittal and EBT2 film measurements were within 67%/64 mm of the TPS. The RPC thermoluminescent dosemeter measurements of the prostate and femoral heads were within 3% of the TPS. Conclusion: The RPC prostate phantom is a useful mechanism to evaluate spot scanning beam proton therapy within certain confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…This study describes dosimetric commissioning tests used for the Varian ProBeam system at MPTC and SPTC and provides results that can be used as a reference for future ProBeam sites. Although the tests described here are not complete, they are similar to those used before and should provide useful benchmarks.…”
Section: Introductionmentioning
confidence: 99%
“…This study describes dosimetric commissioning tests used for the Varian ProBeam system at MPTC and SPTC and provides results that can be used as a reference for future ProBeam sites. Although the tests described here are not complete, they are similar to those used before and should provide useful benchmarks.…”
Section: Introductionmentioning
confidence: 99%
“…When considering how to most effectively treat patients with proton therapy, different treatment planning system provide different advantages and disadvantages . These differences in different treatment planning systems were discussed in various articles for photons and for protons . Pencil beam scanning can also be simulated with Monte Carlo models, although this is more time consuming and not practical for everyday treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on comprehensive PSQA programs for patients receiving particle therapy is limited [ 6 , 8 , 9 ]. Some publications have reported only specific aspects of PSQA [ 10 , 11 , 12 , 13 , 14 , 15 ]. For example, some works focused on either dosimetric detector development or evaluation: Karger et al [ 13 ] developed a detector based on a block of ionization chambers for 3D dosimetric verification of treatment plans in intensity-modulated heavy ion therapy, and Arjomandy et al [ 10 ] reported the use of a 2D-ICAD for verification of patient-specific dose distributions in proton therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies investigated the validation of the TPS for particle therapy. Iqbal et al [ 11 ] reported QA evaluation of SSPT with an anthropomorphic prostate phantom, and Jäkel et al [ 12 ] published QA for a TPS for scanned ion beam therapy. Lomax et al [ 6 ] summarized their experience with an SSPT PSQA program, which included treatment field-specific dose verifications, for 166 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation